Ga-Pt supported catalytically active liquid metal solutions (SCALMS) prepared by ultrasonication - influence of synthesis conditions on n-heptane dehydrogenation performance - Oshin, Oshin; Al-Shaibani, Asem; Taccardi, Nicola; Sultan, Umair; Inayat, Alexandra; Vogel, Nicolas; Haumann, Marco; Wasserscheid, Peter (Catalysis: Science and Technology, 2023)
Supported catalytically active liquid metal solution (SCALMS) materials represent a recently developed class of heterogeneous catalysts, where the catalytic reaction takes place at the highly dynamic interface of supported liquid alloys. Ga nuggets were dispersed into nano-droplets in propan-2-ol using ultrasonication followed by the addition of Pt in a galvanic displacement reaction - either directly into the Ga/propan-2-ol dispersion (in situ) or consecutively onto the supported Ga droplets (ex situ). The in situ galvanic displacement reaction between Ga and Pt was studied in three different reaction media, namely propan-2-ol, water, and 20 vol% water containing propan-2-ol. TEM investigations reveal that the Ga-Pt reaction in propan-2-ol resulted in the formation of Pt aggregates on top of Ga nano-droplets. In the water/propan-2-ol mixture, the desired incorporation of Pt into the Ga matrix was achieved. The ex situ prepared Ga-Pt SCALMS were tested in n-heptane dehydrogenation. Ga-Pt SCALMS synthesized in pure alcoholic solution showed equal dehydrogenation and cracking activity. Ga-Pt SCALMS prepared in pure water, in contrast, showed mainly cracking activity due to oxidation of Ga droplets. The Ga-Pt SCALMS material prepared in water/propan-2-ol resulted in high activity, n-heptene selectivity of 63%, and only low cracking tendency. This can be attributed to the supported liquid Ga-Pt alloy where Pt atoms are present in the liquid Ga matrix at the highly dynamic catalytic interfac
Keywords: Binary alloys; Dehydrogenation; Drops; Heptane; Liquid metals; Platinum alloys; Substitution reactions; Cracking activity; Ex situ; Galvanic displacement reactions; matrix; Metal solutions; n-Heptanes; Nano-droplets; Performance; Synthesis conditions; Ultra-sonication; Catalysis